(3GdebUO GdCQTO aj JQGLe CUMGH GdEeGe CMeOs - (3GHf eadM , EHQGgje Hf eMeO Hf YHO Gddg Hf eMeO, HQgGf GdOjf CHh ESMGb,J (B884 (3g` s ((3eMeO UGdM Hf eMeO SYjO YHO GdMajX Hf MeGO s)
(3ChdgG (B:s
(3HYO GdJUOjQ (B: (3hHYO agPG cJGH LeYJg hLYdJg eTJedkG Ydi WHbGJ CUMGH GdEeGe CMeO Hf MfHd s
(3HBNQgG JQLeI ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B65 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B100s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B260 s
Keywords: (3GdJGQjNs